Odpowiedzi

2009-12-06T22:42:05+01:00
(y+1)² -7=(y+3)(y-3)
y²+2y+1-7=y₂-3y+3y-9
2y=-9+6
y=-3:2
4(z-1)²+(2z+3)(3-2z)= -4z+1
4(z²-2z+1)+6z-4z²+9-6z=-4z+1
4z²-8z+4+6z-4z²+9-6z=-4z+1
-8z+13+4z-1=0
-4z=-13/:-4
z=13:4

(x+1)²= (x-1)²-2(x-4)
x²+2x+1=x²-2x+1-2x+8
2x+2x+2x=9-1
6x=8
x=8:6


2x-11:4+19-2x:2=2x mnożymy każdy wyraz przez 4
8x-11+76-4x=8x
-4x=-65
x=16,25
2009-12-06T22:45:33+01:00
(y+1)² -7=(y+3)(y-3)
y²+2y+1-7=y²+9
2y=16 |:2
y=8

4(z-1)²+(2z+3)(3-2z)= -4z+1
(8-4)²+(3+2z)(3-2z)=-4z+1
64-64+9+4z=-4z+1
4z+4z=1-9
8z=-8
z=-1

(x+1)²= (x-1)²-2(x-4)
x²+2x+1=x²-2x+1-2x+8
6x=8 |:6
x=1⅓
2009-12-06T22:46:25+01:00
(y+1)² -7=(y+3)(y-3)
y²+2y+1-7=y²-9
2y=-3 /:2
y=-1½

4(z-1)²+(2z+3)(3-2z)= -4z+1
4z²-8z+4-4z²+9=-4z+1
-4z=-12 /: (-4)
z=3

(x+1)²= (x-1)²-2(x-4)
x²+2x+1=x²-2x+1-2x+8
6x=8 / :6
x=1⅓

3-2x:5+8=5x+2:2-x dołóż nawiasy